Paraben residues in wastewater and surface water: a case study of KwaZulu Natal and Gauteng provinces (South Africa) during the COVID-19 pandemic - Mpayipheli, Neliswa; Mpupa, Anele; Madala, Ntakadzeni Edwin; Nomngongo, Philiswa Nosizo (Frontiers in Environmental Science, 2024)
Introduction: The presence of pharmaceuticals and personal care products in environmental matrices is considered one of the major scientific concerns. Most of these substances are disposed of unchanged through wastewater treatment plants and sewage systems. Consequently, they are continuously introduced into the water systems and progressively contaminate surface, ground and drinking water. During the COVID-19 pandemic, a large number of emerging contaminants including parabens were released to the environment through various routes. In this study, the occurrence of parabens (methylparaben (MePB), ethylparaben (EtPB), propylparaben (PrPB), and butylparaben (BuPB) was investigated in wastewater samples from various wastewater treatment plants (WWTPs) and the receiving surface waters in KwaZulu Natal and Gauteng Provinces (South Africa). Methods: The samples were collected between October 2020 and December 2021, covering the 2nd, 3rd and 4th waves of the COVID-19 pandemic. A solid phase extraction protocol with high-performance liquid chromatography was used to extract and enrich parabens before analysis. Results and Discussion: Methylparaben (2.02–84.7 μg/L), EtPB (<0.24–24.8 μg/L), PrPB (<0.26–55.1 μg/L), and BuPB (<0.27–17.3 μg/L) were quantified in wastewater influent collected WWTPs of KwaZulu Natal Province. While <0.19–5.43 μg/L, <0.16–5.63 μg/L, <0.17–6.89 μg/L, and <0.19–5.32 μg/L for MePB, EtPB, PrPB, and BuPB, respectively, were quantified in effluent wastewater from the same province. The concentrations of MePB, EtPB, PrPB, and BuPB in influent wastewater from Gauteng Province were 2.58–123 μg/L, <0.24–33.6 μg/L, 3.77–73.4 μg/L and <0.27–85.8 μg/L, respectively. In effluent wastewater, concentrations ranging from 0.24–17.76 μg/L (MePB), <0.16–4.88 μg/L (EtPB), 0.69-12.5 μg/L (PrPB), and <0.19–4.726 μg/L (BuPB) were quantified. During the 4th wave, the concentrations of parabens in surface water were lower compared to the second and third waves of the pandemic. In general, the paraben residues in the surface of KwaZulu Natal Province (<0.08–16.4 μg/L) were higher than those in Gauteng Province (0.08-3.14 µg/L). Methylparaben and propylparaben were dominant in all investigated samples (wastewater and surface water), followed by ethylparaben. The ecotoxicological risk assessment was carried out for aquatic biota, which was estimated in terms of risk quotients (RQs). RQs for the target compounds in river water indicated that MePB and EtPB pose low risk, whereas PrPB and BuPB pose low to medium risk to aquatic organisms.